Antibiotic sensitivity and in vitro antimicrobial activity of plant extracts to pseudomonas fluorescens isolates collected from diseased fish - Foysal, MJ; Rahman, MM; Alam, M (International Journal of Natural Sciences, 2012)
Studies were conducted to identify Pseudomonas fluorescens isolates from a collection of bacteria isolated from bacterial haemorrhagic septicaemia infected carp and catfish, evaluate their antibiotic sensitivity pattern and screen the antibacterial activity of some medicinal plant extracts against the isolates.. A total of 10 isolates were identified as P. fluorescens by morphological, physiological and biochemical tests. In vitro antibiotic sensitivity test of the P. fluorescens isolates were conducted by disc diffusion method for seven antibiotics where, all of the isolates were found to be sensitive only against streptomycin and gentamycin but, most of the isolates (80%) were found resistant to chloramphenicol (C). Moreover, eighty percent of the isolates showed resistance to multiple antibiotics. A total of 118 plant extracts were screened for their antibacterial activity against the P. fluorescens isolates where the isolates exhibited sensitivity to 30 samples. Leaf extracts of Tamarindus indicus, Terminalia chebula, Citrus aurantifolia, Eugenia caryophyllata and Spondias pinnata were found to inhibit the growth of all of the P. fluorescens isolates. DOI: http://dx.doi.org/10.3329/ijns.v1i4.9733 IJNS 2011 1(4): 82-88